2022
DOI: 10.56600/jwmdc.v1i3.42
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Upper Cross Syndrome In Medical Students of Women Medical College, Abbottabad, Khyber Pakhtunkhwa, Pakistan

Abstract: Upper Cross Syndrome is a common muscular imbalance involving head, neck and shoulder region. It exhibits a common postural disruption linked with tonal abnormalities of the pectoral girdle musculature and cervicothoracic part of the body. This syndrome is characterized by neck pain and its restricted range of motion, forward head posture and rounded shoulders. It is usually seen in persons who work for longer period of time in misaligned body position. This study was intended to check the prevalence of Upper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 2 publications
2
9
0
Order By: Relevance
“…This study highlighted that empathy was significantly associated not only with age, but also with gender: females had a higher mean empathy score than males. Regarding gender, this result is in line with numerous other studies among dental students (Aggarwal et al, 2016; Carvajal et al, 2019; Díaz‐Narváez et al, 2018; Javed, 2019; Michael et al, 2019; Sherman & Cramer, 2005). Several explanations have been given for gender differences in empathy, including social learning, genetic predisposition, evolutionary underpinnings, higher capability of females to identify emotional signals and to better understand relationship situations (Brekalo Prso et al, 2020; Hojat et al, 2018; Michael et al, 2019).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This study highlighted that empathy was significantly associated not only with age, but also with gender: females had a higher mean empathy score than males. Regarding gender, this result is in line with numerous other studies among dental students (Aggarwal et al, 2016; Carvajal et al, 2019; Díaz‐Narváez et al, 2018; Javed, 2019; Michael et al, 2019; Sherman & Cramer, 2005). Several explanations have been given for gender differences in empathy, including social learning, genetic predisposition, evolutionary underpinnings, higher capability of females to identify emotional signals and to better understand relationship situations (Brekalo Prso et al, 2020; Hojat et al, 2018; Michael et al, 2019).…”
Section: Discussionsupporting
confidence: 90%
“…In this study, the empathy score of dental students seemed to decline from the fourth to the sixth year of study, but not significantly. This tendency of the empathy scores appears inconsistent in the literature: Some studies showed an erosion of empathy with the clinical experience of dental students (Aggarwal et al, 2016; Datta et al, 2016), while others showed a nonsignificant increase of empathy during this study period (Ameh et al, 2019; Brekalo Prso et al, 2020; Javed, 2019). The decline during clinical training may be attributed to a greater priority on students' needs to acquire technical skills for dental care procedures.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Most of the literature produced on topic was biased which supported one or other discourse, however, a more balanced view is also provided in some of the recent literature on the topic. Among those authors who supported the Pakistani state discourse portraying Mohammad Bin Qasim as a hero are (Ahmed, 1958;Qureshi, 1962;Siddiqi, 1969;Anver, 1979;Quddus, 1992;Haroon, 2004;Kazimi, 2007;Javed, 2010) are only a few to name here.…”
Section: Review Of Literaturementioning
confidence: 99%